Kreativitas Guru PAI dalam Membentuk Karakter Peduli Lingkungan di SMP Nurul Hadina Patumbak - Putri Maymuhamna Rahayu; Arlina Arlina; Enny Nazrah Pulungan (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2024)
The research that has been carried out is entitled "Creativity of PAI Teachers in Forming Environmentally Caring Character at Nurul Hadina Patumbak Middle School" which is based on the fact that currently there is still some evidence that shows that students' concern for the school environment is still minimal, namely that there are still some students who throw rubbish carelessly After having snacks from small stalls around the school, the classroom yard still looked dirty, and students did not picket. So with the creativity of PAI teachers, researchers want to see or research what creativity PAI teachers use in forming students' environmentally caring character at Nurul Hadina Middle School, Patumbak. This research uses qualitative research methods with descriptive research type and data collection techniques, namely observation, interviews and documentation. In data analysis there are three steps carried out, namely data reduction (collecting data), data display (presenting data), and verification (drawing conclusion). The results of the research reveal that PAI teachers' creativity in forming environmentally caring character at Nurul Hadina Patumbak Middle School can be classified by carrying out habituation activities, providing warnings and advice, and leading by example. The habituation activities carried out include getting used to collecting rubbish, picketing, cleaning toilets and caring for plants.